2019
DOI: 10.24059/olj.v23i1.1419
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the Construct Validity and Causal Relationships of Teaching, Cognitive and Social Presence in Community of Inquiry Framework

Abstract: Despite the prevalence of research on the Community of Inquiry framework and its associated measurement instrument, more research is needed to re-evaluate the factor structure, study the effects of covariates or measurement invariance, and explore the relationships among the three presences. Results of this study indicated that (a) teaching, social, and cognitive presence are each multidimensional and higher order constructs; (b) measurement invariance was fully achieved for gender and partially for age, ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
6
34
1
Order By: Relevance
“…We found no demographic predictors significantly predicted CoI scale variables during emergency remote learning. This is in contrast with past research in which the demographics such as ethnicity, gender, and discipline significantly impacted CoI variables in online courses (Dempsey & Zhang, 2019;Wicks, Craft, Mason, Gritter, & Bolding, 2015) and past research showing demographic differences in students' adaptability to online learning (Xu & Jaggars, 2013). It is plausible that our sample lacked the diversity and sample size to make differences apparent, or that the accommodations and multimodal support provided by instructors created equitable learning environments.…”
Section: Student Educational Experiencecontrasting
confidence: 80%
“…We found no demographic predictors significantly predicted CoI scale variables during emergency remote learning. This is in contrast with past research in which the demographics such as ethnicity, gender, and discipline significantly impacted CoI variables in online courses (Dempsey & Zhang, 2019;Wicks, Craft, Mason, Gritter, & Bolding, 2015) and past research showing demographic differences in students' adaptability to online learning (Xu & Jaggars, 2013). It is plausible that our sample lacked the diversity and sample size to make differences apparent, or that the accommodations and multimodal support provided by instructors created equitable learning environments.…”
Section: Student Educational Experiencecontrasting
confidence: 80%
“…Also, there was a significant research gap in exploring the effect of satisfaction level of students regarding network speed for online learning, particularly framed by the CoI elements; no previous work was found that evaluated whether gender and academic discipline moderated the association between the satisfaction level of students regarding network/Internet speed for online education/learning considering the CoI elements. Furthermore, most CoI research studies (e.g., Arbaugh et al, 2010;Garrison et al, 2010a,b;Carlon et al, 2012;Arbaugh, 2013;Dempsey and Zhang, 2019;Heilporn and Lakhal, 2020) used data from undergraduate and postgraduate samples. The context of Hong Kong sub-degree students has been seriously overlooked even though it represents a large student population and is considered a unique education sector in the academic world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, The Community of Inquiry has been used effectively to examine learning experiences and to compare different learning environments in many contexts (Stenbom, 2018). The combined result of Stenbom's systematic review is that the Community of Inquiry Survey is a widely accepted tool for revealing learners' perceptions of learning experience, and its measurement invariance was tested for many variables (gender, age, ethnicity, discipline, online experience) (Dempsey & Zhang, 2019). So, it is a guide for the design of courses (Akyol, Vaughan, & Garrison, 2011;Swan, Day, Bogle, & Matthews, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to evaluate the effectiveness of online learning courses based on Community of Inquiry Model. This model, providing insights for instructors on the strengths or weaknesses of a course (Dempsey & Zhang, 2019;Lambert & Fisher, 2013), can produce special practices that include facilitating elements of learning such as affective explanations, group discussions, research activities and course organization to create a more attractive and engaging course. While examining the effectiveness of online courses based on the Community of Inquiry, it can be stated that learner characteristics and satisfaction variables are still worth examining due to inconsistent results in the literature.…”
Section: Introductionmentioning
confidence: 99%